2016
DOI: 10.1128/jb.00118-16
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic Studies of Biofilm Formation in Dynamic Environments

Abstract: bThe advent of microscale technologies, such as microfluidics, has revolutionized many areas of biology yet has only recently begun to impact the field of bacterial biofilms. By enabling accurate control and manipulation of physical and chemical conditions, these new microscale approaches afford the ability to combine important features of natural and artificial microbial habitats, such as fluid flow and ephemeral nutrient sources, with an unprecedented level of flexibility and quantification. Here, we review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
60
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(64 citation statements)
references
References 60 publications
(62 reference statements)
1
60
0
Order By: Relevance
“…Some studies indicate that it is not the growth conditions themselves but rather the expression of phenol-soluble modulin (PSM) surfactant peptides that is the key structuring factor for S. aureus and may be pivotal for biofilm strength and thickness [113]. On the other hand, Kim et al have found that fluid flow represses the internal signaling (quorum sensing) of S. aureus, which can be associated with the elution of signaling molecules [114,115]. Nevertheless, several methods based on continuous flow have been introduced [116,117].…”
Section: Flow Systemsmentioning
confidence: 99%
“…Some studies indicate that it is not the growth conditions themselves but rather the expression of phenol-soluble modulin (PSM) surfactant peptides that is the key structuring factor for S. aureus and may be pivotal for biofilm strength and thickness [113]. On the other hand, Kim et al have found that fluid flow represses the internal signaling (quorum sensing) of S. aureus, which can be associated with the elution of signaling molecules [114,115]. Nevertheless, several methods based on continuous flow have been introduced [116,117].…”
Section: Flow Systemsmentioning
confidence: 99%
“…Such a strong interaction between biological processes and microfluidics is very far from being understood. Insights for a deeper comprehension of the mechanisms (mechanical and biological) involved in the biofilm growth can arise from a multidisciplinary approach involving (1) laboratory microfluidic experiments under flow controlled conditions [10], (2) noninvasive imaging methods for assessing the biomass evolution [11], and (3) 3D numerical models [12] coupling biofilm growth and pore-scale fluid dynamics models [13].…”
Section: Next Challengesmentioning
confidence: 99%
“…Later in development, flow provides nutrients to surface-attached biofilm communities, removes metabolic waste products and affects quorum sensing molecules [8][9][10]. There is therefore intense practical and theoretical interest in understanding the interaction between biofilms and external flow fields [8,11]. Identifying the multi-scale dynamics of such growth-active nematics under the influence of shear will be helpful when adapting current theories for active matter [12,13] to describe and predict bacterial biofilm growth across model systems and species [14,15].…”
Section: Introductionmentioning
confidence: 99%